2019
DOI: 10.1111/beer.12229
|View full text |Cite
|
Sign up to set email alerts
|

Environmental entrepreneurship as a multi‐component and dynamic construct: Duality of goals, environmental agency, and environmental value creation

Abstract: Environmental entrepreneurship (EE) is a scholarly field that has gained traction in recent years under the premise that it might represent a solution to pressing environmental grand challenges. Despite substantial advances in recent decades, the field still lacks consensus on the conceptualization of EE. The lack of a settled and unified notion of EE hinders the progress of the field because it challenges EE’s legitimacy, hampers theoretical development, creates measurement, and empirical problems. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 90 publications
(243 reference statements)
0
22
0
4
Order By: Relevance
“…Our study not only validates the efficacy of imprinting theory in explaining individual and organizational behavior but also contributes to the existing literature on the antecedents of firms' environmental performance and voluntary pro-environmental behaviors. This study joins a growing body of literature that emphasizes the role of the CEO in the firm's environmental performance and pro-environmental behaviors (e.g., Antolin-Lopez et al, 2019;Berrone et al, 2010;Berrone & Gomez-Mejia, 2009;Rivera & Leon, 2005;Walls & Berrone, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our study not only validates the efficacy of imprinting theory in explaining individual and organizational behavior but also contributes to the existing literature on the antecedents of firms' environmental performance and voluntary pro-environmental behaviors. This study joins a growing body of literature that emphasizes the role of the CEO in the firm's environmental performance and pro-environmental behaviors (e.g., Antolin-Lopez et al, 2019;Berrone et al, 2010;Berrone & Gomez-Mejia, 2009;Rivera & Leon, 2005;Walls & Berrone, 2015;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 78%
“…As a firm's strategies and behaviors tend to reflect its top executives’ cognitive bases and values (Hambrick & Mason, 1984), prior literature has also documented the significant role of the CEO in the firm's environmental performance or voluntary pro‐environmental behaviors. For example, research has found that the characteristics of CEOs, including pay (Berrone & Gomez‐Mejia, 2009), ownership (Berrone et al., 2010), education (Rivera & Leon, 2005), environmental expertise (Rivera & Leon, 2005), power (Walls & Berrone, 2015), political connection (Wang et al., 2018), and entrepreneurial mindset (Antolin‐Lopez et al., 2019), are all associated with firms’ environmental performance or pro‐environmental behaviors. Despite those endeavors, however, our knowledge about what types of CEOs may have pro‐environmental cognitive bases or values and where such cognitive values may come from remains rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental value is often regarded as gains in environmental efficiency such as more efficient use of resources as well as eco‐effectiveness, which is described as a positive effect beyond efficiency gains (Antolin‐Lopez et al . 2019; Volery 2002). Examples of initiatives that lead to environmental value creation are reforestation programmes, carbon emission neutralization programmes, use of raw materials from renewable sources and investments in preservation and environmental education (Eidelwein et al .…”
Section: Theory: Generating and Internalizing Value By Environmental mentioning
confidence: 99%
“…The frequency of extreme weather events has increased along with global warming, causing a series of serious effects on human health, especially on urban residents [1,2]. By 2050, 6.252 billion people will be living in cities around the world.…”
Section: Introductionmentioning
confidence: 99%